2013
DOI: 10.1002/dc.22975
|View full text |Cite
|
Sign up to set email alerts
|

Psammoma bodies and abundant stromal amyloid in an endoscopic ultrasound guided fine needle aspirate (EUS‐FNA) of a pancreatic neuroendocrine tumor: A potential pitfall

Abstract: A 42-year-old male presented to our institution with a 2-month history of several episodes of confusion, double vision, headache, and loss of consciousness. The blood glucose levels measured during these episodes were in the range of 30-40 mg/dl, but randomly drawn blood samples showed normal glucose levels. Further workup showed a fasting blood glucose level of 34 mg/dl at 60 hours and elevated proinsulin levels, while insulin and C-peptide levels were normal. Serum levels of chromogranin A, pancreatic polype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Their cytomorphology is variable including oncocytic, hepatoid, lipid-rich, plasmacytoid, ductuloinsular, pleomorphic, and paraganglioma-like [ 51 ]. Pancreatic NETs are rarely associated with psammoma bodies and stromal amyloid deposition [ 52 ]. A study found that the detection rates of INSM1, CG, and SYN were 100%, 95%, and 100%, respectively [ 53 ].…”
Section: Insm1 Expression In Pancreatic Netsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their cytomorphology is variable including oncocytic, hepatoid, lipid-rich, plasmacytoid, ductuloinsular, pleomorphic, and paraganglioma-like [ 51 ]. Pancreatic NETs are rarely associated with psammoma bodies and stromal amyloid deposition [ 52 ]. A study found that the detection rates of INSM1, CG, and SYN were 100%, 95%, and 100%, respectively [ 53 ].…”
Section: Insm1 Expression In Pancreatic Netsmentioning
confidence: 99%
“…Pancreatic specimens may pose diagnostic challenges as well, due to nuclear expression of INSM1 in islet cells (pancreatic neuroendocrine cells) [ 25 ]. In addition, normal cortical adrenal cells and also a very small percentage of prostate cells are positive for INSM1 [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Insm1 Expression In Non-neuroendocrine Neoplastic and Non-neoplastic Cellsmentioning
confidence: 99%
“…Hematologic malignancies and medullary thyroid carcinoma are two neoplasms that are known to cause amyloid deposition where medullary thyroid carcinoma causes calcitonin type amyloid and plasma cell dyscrasia and some types of lymphoma can cause immunoglobulin related amyloidosis [36]. Amyloid deposition has also been reported in association with other epithelial neoplasms including urothelial carcinoma, neuroendocrine tumors, pituitary adenoma, gastric carcinoma, nasopharyngeal carcinoma, breast carcinoma, and endometrioid carcinoma and rarely in association with sarcomas including Kaposi's sarcoma, follicular dendritic cell sarcoma, leiomyosarcoma, and pleomorphic sarcoma [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. e relationship between the amyloid and most of the previously mentioned neoplasms, however, is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In FNAs other than the fat‐pad aspirates, amyloid is a rare, and almost always unexpected finding. Despite this, it has been identified in FNA (including EBUS‐TBNA) samples from various anatomical sites, including lung, mediastinum, nasopharynx, breast, skin, and bone, either by itself or associated with various tumors (medullary thyroid carcinoma, neuroendocrine tumors, plasmacytoma/myeloma, and lymphoma) …”
mentioning
confidence: 99%